Involvement Of Azotobacter Vinelandii Hypothetical Protein Avin_16040 In Oryza Sativa Root Attachment - Pauline, Liew Woan Ying (2013)
In this study, the dynamic changes of Azotobacter vinelandii ATCC 12837's proteome in response to Oryza sativa L. cv. MR 219, a local rice variety, was observed. Analysis by 2DE MS/MS revealed various protein spots which showed differential presence when A. vinelandii ATCC 12837 was grown in the N-enriched (+N) or N-free (-N) media. Similar experimental setup was also applied to study the profiles when the bacterial strain was exposed to root. The differentially-present intracellular proteins were identified by MALDI-TOF/TOF analysis and these included those involved in metal ion transport and storage, respiration, stress response, structure, regulatory, amino acid synthesis, and electron transport. The identified differentiated extracellular proteins were membrane protein transporters, lipoprotein and oxygen stress response proteins. Besides that, several hypothetical proteins with unknown function were also differentiated. Some of these bacterial proteins demonstrated induced expression under N deficient conditions. There are also a number of other proteins that showed differential presence when A. vinelandii ATCC 12837 was exposed to rice roots compared to those unexposed. The hypothetical protein Avin_16040, which showed exclusive presence when A. vinelandii ATCC 12837 colonized root surface, was further analyzed. To investigate the biological function of Avin_16040, a deletion mutant of the Avin_16040 gene was generated by homologous recombination.